Induction of acute phase proteins in the salivary gland of rats - Wei Wei; Parvin Most. Nahid; 津村恵子; 松浦幸子; 赤松徹也; 多田淳; 金森憲雄; 細井和雄 (Japanese Journal of Oral Biology, 2000)
[Purpose] C-reactive protein (CRP), serum amyloid P component (SAP), and kininogens (KGs) are acute phase proteins which serum levels in humans and murine rise several hundred-folds by acute inflammation and decrease rapidly during healing. CRP opsonizes bacteria, representing a pivotal role in the defense system. In this study we have evaluated the local regulation of these proteins in the gland tissues during acute inflammation. [Materials and Methods] The submandibular gland (SMG) and other gland tissues were removed at 6, 12, 24, and 48h after injection of turpentine oil. The expression of mRNA for the acute phase proteins and TNF-α were measured by the RT-PCR react ion. [Result. and Conclusion] Express ion of mRNAs for CRP, SAP, H- and T-KGs were induced in the 5MG, lacrimal glands, and liver at 24 hours after sc. injection of turpentineoil. This inductionwasprecededbya transient increase of TNF-α mRNA at 6 hours after injection of the same inducer. The up-regulation of acute phase proteins in the exocrine gland suggest the existence of a strict defense system in the gland tissues.